2020
DOI: 10.1038/s41598-020-59210-0
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific genetic variation in response to deep-sea environmental variation amongst Vulnerable Marine Ecosystem indicator taxa

Abstract: Understanding the ecological processes that shape spatial genetic patterns of population structure is critical for understanding evolutionary dynamics and defining significant evolutionary and management units in the deep sea. Here, the role of environmental factors (topographic, physico-chemical and biological) in shaping the population genetic structure of four deep-sea habitat-forming species (one sponge -Poecillastra laminaris, three corals -Goniocorella dumosa, Madrepora oculata, Solenosmilia variabilis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…The discordance found in estimates of population structure across co‐distributed species indicates the importance of both lineage‐specific functional traits and local demographic fluctuations in driving large‐scale patterns of intraspecific genetic variation. In fact, a pattern based on dispersal propensity is apparent here, revealing how environmental factors had different effects on the genetic variation of co‐distributed species that differ in functional traits (Zeng et al., 2020). The mayflies, which show weak dispersal propensity, presumably attributable to their short adult life span, did generally show higher estimates of Φ ST than the highly dispersive co‐distributed beetles.…”
Section: Discusionmentioning
confidence: 83%
“…The discordance found in estimates of population structure across co‐distributed species indicates the importance of both lineage‐specific functional traits and local demographic fluctuations in driving large‐scale patterns of intraspecific genetic variation. In fact, a pattern based on dispersal propensity is apparent here, revealing how environmental factors had different effects on the genetic variation of co‐distributed species that differ in functional traits (Zeng et al., 2020). The mayflies, which show weak dispersal propensity, presumably attributable to their short adult life span, did generally show higher estimates of Φ ST than the highly dispersive co‐distributed beetles.…”
Section: Discusionmentioning
confidence: 83%
“…TA B L E 2 Each indicator taxon, the zone it belongs to, its common and scientific name, number of individuals observed in the 2017 visual surveys, the mean (µ) and standard deviation (σ) of its depth range (2017), its vertical distribution-weighted mean oxygen level and trend (1960-2019); its vertical distribution-weighted mean calcite and aragonite saturation states (Ω (Donachy & Watabe, 1986;Dupont et al, 2008Dupont et al, , 2010Wood et al, 2008 (Leys et al, 2004;Whitney et al, 2005) No calcium carbonate (silicious); presumed insensitive to OA (Bindoff et al 2019;Conway et al, 2017); no direct OA studies (Haigh et al, 2015) TA B L E 2 (Continued) (Austin et al, 2007;Leys et al, 2007) Sensitive to but tolerant of low O 2 (Leys & Kahn, 2018); influences population structure (Zeng et al, 2020); rare at O 2 ~<1.4-2.1 ml/L (Leys et al, 2004;Whitney et al, 2005) No calcium carbonate (silicious); presumed insensitive to OA (Bindoff et al 2019;Conway et al, 2017); no direct OA studies (Haigh et al, 2015) All TA B L E 2 (Continued) the three shallowest seamounts, while the undulated glass sponge inhabited all four (S5).…”
Section: Seamount Indicator Taxa Their Depth Ranges and The Chemimentioning
confidence: 99%
“…The keystone brittle star Ophiothrix fragilis is especially sensitive to OA, with 100% mortality of larvae with a modest increase in acidity (pH = 7.9; Dupont, Havenhand, Thorndyke, Peck, & Thorndyke, 2008). In a recent seascape genetics study, water chemistry in the North Atlantic was identified as a driver of genetic variability in cold water coral and sponge populations (Zeng, Rowden, Clark, & Gardner, 2020), indicating changes in Ω (and oxygen) over space and time could influence population connectivity and structure by creating or removing genetic barriers.…”
Section: Ocean Acidification Impacts On Larvae and Dispersalmentioning
confidence: 99%
“…This is one reason why scientists worldwide should pay special attention to the understanding of environmental data and its collection, because this information can give rise to significant predictors for the observed genetic variability. Among other uses, this can provide valuable information for decision making related to marine organisms, i.e., setting of management areas for conservation (Zeng et al, 2020).…”
Section: Seascape Genetics: Background and General Patternsmentioning
confidence: 99%
“…Subsequently, Silva & Gardner (2016) reported for the New Zealand scallop (Pecten novaezelandiae) that variation in population genetic structure was associated with variation in localised freshwater input and suspended particulate matter concentration. Finally, Zeng et al (2020), working with four deep-sea species in the New Zealand region reported a relationship between variation in dissolved oxygen and genetic variation for a sponge (Poecillastra laminaris), and between dynamic topography (Goniocorella dumosa), sea surface temperature (Madrepora oculata) and tidal current (Solenosmilia variabilis) for genetic variation in three cold-water corals. These studies provide valuable new insights into the key environmental drivers of genetic differentiation among populations, setting a precedent for future research worldwide.…”
Section: Seascape Genetics: Background and General Patternsmentioning
confidence: 99%